The Effectiveness of the Gampong Qanun on the Care and Control of Livestock in Gampong Cot Seurani, Muara Batu District, North Aceh - Fauzah Nur Aksa; T Saifullah; Johan (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This paper examines the application of qanuns regarding the maintenance and control of livestock in the village of Cot Seurani, Muara Batu District, North Aceh. Therefore, to understand the application of the qanun, this paper uses the perspective of legal effectiveness. The study of legal effectiveness carried out in this study basically follows Soerjono Soekanto's opinion in which according to him, the benchmark for the study of legal effectiveness boils down to 5 (five) factors, namely: the content of a law, law enforcement, facilities and infrastructure that support law enforcement, society and the culture of the society in which a law is enacted. The interweaving of these five factors becomes a measure of whether a law is effective or not. The research problem answered in this study is how effective the implementation of the qanun is. In this paper, the approach used is a qualitative approach with the socio-legal method. Research data were collected through in-depth interviews, observation, and literature review. The research results show that prior to implementation, the qanun had been disseminated to all village communities through announcements at meetings, banners attached to walls at several village road points, and also through social media groups. Since the enactment of the qanun, it has had a positive impact in accordance with its objectives. Every perpetrator who violates the qanun will be tried in a customary court. Sanctions given in the form of fines and compensation. The response of the village community to the qanun regarding the control of livestock was very good, because they also felt it was important that there were regulations regarding this matter.